Algebra 1

Published by Prentice Hall
ISBN 10: 0133500403
ISBN 13: 978-0-13350-040-0

Chapter 7 - Exponents and Exponential Functions - Concept Byte - Powers of Powers and Powers of Products - Page 432: 12


$=pq \cdot pq \cdot pq \cdot pq = (p \cdot p \cdot p \cdot p)(q \cdot q \cdot q \cdot q) = p^4q^4$

Work Step by Step

$a^m \cdot a^n = a^{m+n}$ Use the rule above to obtain: $(pq)^4=pq \cdot pq \cdot pq \cdot pq = (p \cdot p \cdot p \cdot p)(q \cdot q \cdot q \cdot q) = p^4q^4$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.